2019
DOI: 10.3389/fphys.2019.00866
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide Exacerbates Cardiac Fibrosis via Activating the NLRP3 Inflammasome

Abstract: Background/Aims: Gut microbiota has been reported to correlate with a higher mortality and worse prognosis of cardiovascular diseases. Trimethylamine N-oxide (TMAO) is a gut microbiota-dependent metabolite of specific dietary nutrients, which is linked to cardiac fibrosis. Recent reports have suggested that the activation of Nucleotide-binding oligomerization domain (NOD)-like receptor protein 3 (NLRP3) inflammasome contributed to cardiac fibrosis. However, whether TMAO mediates cardiac fibrosis via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 57 publications
1
73
0
2
Order By: Relevance
“…The upregulated levels of inflammatory cytokines in the ganglionated plexi as a result of the activation of p65 NF-κB signaling might facilitate these effects [ 19 ]. Furthermore, TMAO exacerbated doxorubicin-induced myocardial fibrosis, at least partially via the activation of the nucleotide-binding oligomerization domain-like receptor protein 3 inflammasome [ 21 ]. These epidemiological studies, as well as animal experiments, have demonstrated the crucial role of TMAO in promoting AF development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulated levels of inflammatory cytokines in the ganglionated plexi as a result of the activation of p65 NF-κB signaling might facilitate these effects [ 19 ]. Furthermore, TMAO exacerbated doxorubicin-induced myocardial fibrosis, at least partially via the activation of the nucleotide-binding oligomerization domain-like receptor protein 3 inflammasome [ 21 ]. These epidemiological studies, as well as animal experiments, have demonstrated the crucial role of TMAO in promoting AF development.…”
Section: Discussionmentioning
confidence: 99%
“…Several researches have reported the linkage between TMAO and the progression of AF diseases [ 18 20 ]. TMAO increases the instability of atrial electrophysiology, induces acute electrical remodeling, and aggravates cardiac fibrosis, thereby facilitating the progression of AF [ 19 , 21 ]. However, relevant bacterial species and metabolic pathways underlying TMAO production in the gut of AF patients and whether TMAO serves as a pathological link between disordered GM and AF are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…TMAO prolongs the effect of angiotensin, eventually leading to adverse cardiac remodelling (Ufnal, et al , ). Another mechanistic link is that TMAO promotes myocardial fibrosis via activation of NLRP3 inflammasome‐associated TGF‐β/Smad3 signalling; in addition, the finding that NLRP3 silencing can abolish the increases in the levels of IL‐1β, TGF‐β and other profibrotic markers induced by TMAO in cardiac fibroblasts (Li, et al , ) suggests that TMAO could be a new potential target for retarding the development of myocardial remodelling and the progression of myocardial functional impairment (Table ).…”
Section: Interactions Between the Gut Microbiota And Cvdmentioning
confidence: 99%
“…Elevated levels of pro-inflammatory cytokines secondary to NLRP-3 inflammasome activation, such as IL-1β, are often detected in elderly individuals correlating with age-related CVD [ 38 , 73 ]. Indeed, the formation of NLRP-3 inflammasome promotes collagen production and IL-1β activation leading to adverse cardiac remodeling and caspase-1 mediated cell death [ 74 , 75 ]. Mature IL-1β promotes the LV expression of pro-fibrotic tumor growth factor β (TGF-β), excessive extracellular matrix (ECM) accumulation and collagen I deposition [ 76 , 77 ].…”
Section: Nlrp3 Inflammasomes In Chronic Inflammation and Heart Faimentioning
confidence: 99%